Kalkkrusten und Karstformenschatz auf Yucatán/México - Gerstenhauer, Armin (ERDKUNDE, 1987)
In the northern part of Yucatan the karst regions are covered by crusts which are conform to the topography of the karst features. These surface-calcretes are developed both on the upper peneplains (where a kegelkarst relief is super-imposed which evolved after the Upper Eocene) and on the lower plain of Upper Pliocene age. A layer in which the limestone is disintegrated into calcareous fine sand is always found under the crust. The thicknesses of both formations correlate with one another. The genesis of these two strata is discussed in detail. The attempt to establish a chronostratigraphy on the basis of geological and geomorphological evidence leads to the conclusion that the crust formation must have started in the younger Paleogene. Furthermore, later periods of incrustation till to the Holocene can be proved. Absolute datings with the help of the 230Th/234U and the ESR dating techniques cover the space of the time until the earliest Pleistocene. The karst forms have mostly been fossilized by the calcretes. The relation between crusts and different forms of the cenotes is pointed out.